Same Mathematical Structure, Different Design: How Does Task Format Affect Creative Problem-Posing Performance? - Özdemir Ercan; Kar Tuğrul; Öçal Tuğba (Sciendo, 2022)
Introduction: The purpose of the study was to investigate the effect of task format on pre-service mathematics teachers' creative problem-posing performance.